Case Report: ROSAH syndrome presents diagnostic and therapeutic challenges - Shunyakova, Jenny; Reynolds, Margaret; Taylor, Amal; Sieck, Erin G.; Walsh, James T.; Hassman, Lynn M. (Frontiers in Ophthalmology, 2025)
BackgroundRetinal dystrophy, optic nerve edema, splenomegaly, anhidrosis, and headache (ROSAH) syndrome is an autosomal dominant disorder caused by a heterozygous missense mutation in alpha kinase 1 (ALPK1). This series reports the presentation and treatment outcomes of three first-degree relatives with ROSAH syndrome.MethodsRetrospective chart review, whole exome sequencing.ResultsA 16-year-old male presented with bilateral optic disc edema, macular edema, retinal degeneration, and vitreous inflammation. His mother and brother had similar clinical features. Whole exome gene sequencing identified a shared heterozygous mutation in the ALPK1 gene c.710C>T, consistent with ROSAH syndrome. Ophthalmic manifestations in this family included optic nerve edema, macular edema, panuveitis, glaucoma, and widespread retinal cone and rod dysfunction. While the proband’s macular edema improved with intravitreal dexamethasone and systemic tocilizumab, immune suppression did not prevent retinal degeneration.ConclusionA diagnosis of ROSAH syndrome, suggested by the concomitant presentation of optic disc edema, uveitis, and retinal degeneration, can be made by targeted genetic sequencing of the ALKP1 gene. While ROSAH-associated ocular inflammation and macular edema may respond to local steroids and immune suppression, retinal degeneration may progress despite these therapies.